ANALISIS BIBLIOMETRIK DAMPAK PENCEMARAN SUNGAI TERHADAP EKOSISTEM AIR - Kasim, Sri Imelda; Longkop, Sutriani Afrilia; Iqbal, Mohammad; Kapi, Florentinus B; Husain, Ilyas H (Universitas Cokroaminoto Palopo, 2025)
River pollution in Indonesia due to industrial and domestic waste threatens water quality and ecosystem health. Many rivers are polluted, which has a negative impact on biodiversity and the quality of life of communities that depend on these water sources. Protection of the hydrological environment is important to maintain ecosystem balance, and cooperation is needed to overcome this problem in order to safeguard water resources. This research uses bibliometric analysis to explore trends and research focus on river pollution and its impacts on aquatic ecosystems. Data was collected from Google Scholar (2020-2024) and filtered based on relevance criteria. Analysis was performed using VosViewer software for network visualization, followed by interpretation of the results to identify future research directions and environmental implications. Research shows an increasing trend in publications regarding the impact of river pollution on aquatic ecosystems from 2020 to 2024, with a total of 3,816 articles. Micro particle pollution and heavy metal pollution are the main themes. The mapping shows six research groups, indicating the need for further research, especially in the Gorontalo area, to improve understanding and treatment of this problem. Research on the impact of river pollution on aquatic ecosystems shows a significant increase in the number of publications from 2020 to 2024, with a total of 3,816 articles. Key topics include microparticle pollution and heavy metals. The mapping shows six theme clusters, highlighting the need for further research, especially in Gorontalo,